2022
DOI: 10.1186/s12877-022-02825-x
|View full text |Cite
|
Sign up to set email alerts
|

Distal radius fractures in the superelderly: an observational study of 8486 cases from the Swedish fracture register

Abstract: Background The distal radius fracture (DRF) is the most common fracture in adults. With an ageing population, the number of wrist fractures in the superelderly (≥ 80 years) is expected to rise. Optimal treatment for displaced DRFs remains controversial, especially in the superelderly group. In addition, basic knowledge of the outcome after a DRF in this heterogenic group is lacking. The aim of this study was to study injury characteristics, treatment and outcome of DRFs in superelderly patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…This allowed us to enroll as many patients as possible overseeing the longest possible observation period. This is in line with previous published studies that also used retrospective designs ( 8 , 13 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This allowed us to enroll as many patients as possible overseeing the longest possible observation period. This is in line with previous published studies that also used retrospective designs ( 8 , 13 15 ).…”
Section: Discussionsupporting
confidence: 92%
“…While results from Swedish fracture registers suggest a more conservative treatment (7,8), German surgeons seem more willing to opt for surgery (3,9). Surgery allows an early start of wrist movement, while casting for 6 weeks is accompanied by muscle loss and often loss of autarky for the elderly.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Previous publications also showed no link between reduction loss and poor functional outcomes. 11 , 23 , 24 , 25 A recent article by Sagerfors et al 26 found that, in general, patient-related outcomes in the elderly (aged >80 years) were poorer 1 year after sustaining a distal radius fracture compared with the prefracture state. However, no difference was found between conservative treatment and volar plating.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] The fracture pattern, surgeon preference and experience, and the literature orientation in any point in time guide hand surgeons in the management of distal radius fractures. [11][12][13][14][15][16] The evidence for best practice needs to be regularly updated through scientific rigor and peer review, a process that has survived the test of time in the surgical world. For this reason, HAND has dedicated a supplemental issue to the research in distal radius fractures highlighting current trends, techniques, and outcomes for hand surgeon's interpretation and resolution in their quest to provide the best possible prevailing care for their patients.…”
Section: Editorialmentioning
confidence: 99%